Improvement The Learning Outcomes Of Physical Fitness In Explosive Strength Of The Lower Limb Muscles Through The Modification Of The Traditional Sack Race Game For Class X-4 Students At SMAN 9 Malang : Penelitian - Afrido Dias Pratama; Winarno; Salamet (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The purpose of this research is to improve the learning outcomes of physical fitness, specifically in the aspect of leg muscle explosiveness among the students of class X-4 at SMA Negeri 9 Malang through the traditional game method of sack racing. This Classroom Action Research (CAR) was conducted in two cycles, consisting of stages of planning, action implementation, observation, and reflection, carried out over 2 cycles with 1 meeting in each cycle. The results of the study indicate an improvement in physical fitness learning outcomes in terms of leg muscle explosiveness from the pre-cycle to the first cycle, and it continued to increase in the second cycle. The initial observation results showed a percentage of 54%, leading to actions taken in cycle 1 with a resulting percentage of 65%, followed by cycle 2 with a resulting percentage of 76%. The traditional sack race game method has proven to be effective as a learning medium that provides stimulation, benchmarks, and motivation for students to perform vertical jumping movements more effectively. This modification creates a more enjoyable and effective learning environment, thereby enhancing the students' long jump learning outcomes.